Indian berry pickers on Vashon Island, June 1943 - University of Washington Libraries
In the summer of 1943, the Vashon Island Packing Company hired 80 First Nations people from British Columbia to weed and harvest strawberries, loganberries, and currants. The Indian workers replaced Filipino workers who were now growing vegetables and working in World War II industries. The Canadian farmworkers earned 50 to 60 cents an hour, reportedly two to three times what they might have made at home. Those who stayed the whole summer had their transportation to and from Canada paid for as well. This June 1943 photo shows some of the Indian workers in a Vashon Island strawberry field. Caption information from "Tribesmen weed berries," Seattle Post-Intelligencer, June 7, 1943, p. 11.